2018
DOI: 10.1111/corg.12235
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance of audit firms: Assessing the usefulness of transparency reports in a Europe‐wide analysis

Abstract: Manuscript Type Empirical Research Question/Issue Based on both institutionalized agency theory and meso‐level theory, this study examines corporate governance disclosure in an audit firm's transparency report (TR) and whether more disclosure is associated with (a) the audit function of the country in which it is disclosed; (b) high levels of investor confidence in public interest entities (PIEs) shown in the portfolio of the audit firm; and (c) increased competition within the audit market. Research Findings/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…Thirdly, control over the implementation of each individual task, the achievement of goals in general, the timing and resources spent on the implementation of the project. Fourthly, audit becomes the basis for the formation of relevant information about the need to make adjustments to management processes in case of their low efficiency, or in order to increase the efficiency of these processes, carry out mobile transformation when conditions change external or internal environment, for example, socio-political or social economic processes (Heald, 2018;Sari et al, 2017;La Rosa et al, 2019).…”
Section: Achievability Of Strategic Objectivesmentioning
confidence: 99%
“…Thirdly, control over the implementation of each individual task, the achievement of goals in general, the timing and resources spent on the implementation of the project. Fourthly, audit becomes the basis for the formation of relevant information about the need to make adjustments to management processes in case of their low efficiency, or in order to increase the efficiency of these processes, carry out mobile transformation when conditions change external or internal environment, for example, socio-political or social economic processes (Heald, 2018;Sari et al, 2017;La Rosa et al, 2019).…”
Section: Achievability Of Strategic Objectivesmentioning
confidence: 99%
“…Apart from the minimum disclosure contents specified in some jurisdictions, the TR has a discretionary nature. Regulators do not favor the implementation of a TR template (POB, 2010), as that decision would be to the detriment of innovative formats that firms may develop for their TR (Deumes et al , 2012; La Rosa et al , 2019). This view is in line with the IAASB approach that TR may assist the users of audited financial statements to understand the characteristics of audit firms and their drivers for audit quality as well as assist entities in selecting a new audit firm (IAASB 2014, para 37).…”
Section: Background and Development Of Research Questionsmentioning
confidence: 99%
“…The international scope of corporate governance research is indicated by the diverse set of governance environments studied in recent CGIR articles that include Australia, Canada, China, Germany, India, Indonesia, Iran, Italy, Japan, Korea, Russia, Spain, Sweden, Taiwan, the United Kingdom, the United States, and Vietnam, as well as multicountry studies (e.g., Deloof, Du, & Vanacker, 2020; Desender, LópezPuertas‐Lamy, Pattitoni, & Petracci, 2020; García‐Sánchez & García‐Meca, 2018; Lazzarini & Musacchio, 2018; Qian, Cao, & Cao, 2018; Tribó, 2019; Zhou & Guillén, 2019). Corporate governance research is by no means restricted to the average publicly held corporation but also deals with the unique challenges associated with specific types of firms like, for instance, audit firms (La Rosa, Caserio, & Bernini, 2019), banks (Sheedy & Griffin, 2018), business groups (Shin, Hyun, Oh, & Yang, 2018), closely held firms (Russino, Picone, & Dagnino, 2019), declining firms (Abebe & Tangpong, 2018), entrepreneurial ventures (Pérez‐Calero, Larrañeta, & Wright, 2019), family firms (Yeh & Liao, 2019), foundations (Thomsen, Poulsen, Børsting, & Kuhn, 2018), institutional investors (Semenova & Hassel, 2019), intergovernmental organizations (Federo & Saz‐Carranza, 2018), initial public offerings (IPOs) (González, Guzmán, Tellez‐Falla, & Trujillo, 2019), as well as state‐owned enterprises (Apriliyanti & Randøy, 2019). This research intensity demonstrates the spread of corporate governance studies in multiple disciplines but also leads to higher levels of fragmentation of the field.…”
Section: Introductionmentioning
confidence: 99%
“…. Corporate governance research is by no means restricted to the average publicly held corporation but also deals with the unique challenges associated with specific types of firms like, for instance, audit firms (La Rosa, Caserio, & Bernini, 2019), banks (Sheedy & Griffin, 2018), business groups (Shin, Hyun, Oh, & Yang, 2018), closely held firms (Russino, Picone, & Dagnino, 2019), declining firms (Abebe & Tangpong, 2018), entrepreneurial ventures (Pérez-Calero, Larrañeta, & Wright, 2019), family firms (Yeh & Liao, 2019), foundations (Thomsen, Poulsen, Børsting, & Kuhn, 2018), institutional investors (Semenova & Hassel, 2019), intergovernmental organizations (Federo & Saz-Carranza, 2018), initial public offerings (IPOs) (González, Guzmán, Tellez-Falla, & Trujillo, 2019), as well as state-owned enterprises (Apriliyanti & Randøy, 2019). This research intensity demonstrates the spread of corporate governance studies in multiple disciplines but also leads to higher levels of fragmentation of the field.…”
mentioning
confidence: 99%